Remote Monitoring Device for Factory Inventory Management by Using IoT - Mohd Nor, Mohd Johan Aiman; Jubadi, Warsuzarina (Evolution in Electrical and Electronic Engineering, 2022)
Commonly in the factory's maintenance department or warehouse, there are storage rooms available to store goods or spare parts. Eventually, it’s not easy, requires much effort, and the warehouse needs more staff to monitor the movement and use of products or assets in their facilities. This manual process could lead to inaccurate stock management and this adds to unnecessary costs to fix the error. In recent years, many warehouse inventory management systems were developed using wireless communication technologies such as Radio Frequency Identification (RFID). The tag information is transferred from the transmitter section to open-source hardware via a wireless link with the aid of the Internet. However, staff still need to monitor the inventory system closely on-site. Hence, to avoid this problem, the automated stock inventory and management using the Internet of Things (IoT) is very helpful because it allows users to remotely monitor product stock without having to go to the shelf where the product is located. Automated stock inventory and management systems using IoT are significant aspects of maintenance and goods-based methodology. The automated stock inventory and management using IoT built on the Internet of Things architecture is developed to track the record of products amount and their respective time stamps for further verification. The NodeMcu acts as a central server, monitoring all the information. The total system can correspond to the information flow and material flow: Thingspeak, which provides a convenient interface for the user to track the products. The developed system results in a very low-cost system. It works dynamically compared with the existing present warehouse inventory management systems.